Few-layer MoS2 and Pt nanoparticles Co-anchored on MWCNTs for efficient hydrogen evolution over a wide pH range. (20th October 2020) - Fan, Aixin; Zheng, Peng; Qin, Congli; Zhang, Xin; Dai, Xiaoping; Ren, Danhua; Fang, Xu; Luan, Chenglong; Yang, Juntao
Highlights: Pt nanoparticles and few-layer MoS2 co-anchored on multiwalled carbon nanotubes facilitated HER. This catalyst can expose more active sites and disperse Pt nanoparticles to prevent agglomeration. This catalyst achieves both high activity and robust durability in 0.5 M H2 SO4, 1.0 M phosphate buffer solution, and 1.0 M KOH, respectively. The DFT demonstrates that the co-existence of MoS2 and Pt facilitate the water dissociation reaction and hydrogen generation, respectively. Abstract: Considering the practical use of electrochemical water splitting, it is important to construct a highly efficient and stable hydrogen evolution reaction (HER) electrocatalyst over a wide pH range. Herein, we develop an efficient strategy to enhance the electrochemical activity of few-layer MoS2 and Pt nanoparticles (NPs) anchored on multi-wall carbon nanotube (MWCNTs). The as-prepared Pt-MoS2 /MWCNTs provides an excellent HER electrocatalytic activity with low overpotentials at −10 mA cm −2 over a wide pH range, namely, 20 mV in 0.5 M H2 SO4, 92 mV in 1.0 M phosphate buffer solution (PBS), and 75 mV in 1.0 M KOH, respectively. In addition, Pt-MoS2 /MWCNTs deliver the highest mass activity at the overpotential of 0.05 V, which is 8.1, 2.3, and 26.5 times higher than that of commercial 20 wt% Pt/C in acidic, neutral and alkaline media, respectively. Density functional theory (DFT) calculations revealed that the co-existence of MoS2 and Pt NPs facilitated the water dissociation reaction and hydrogen generation, thereby enhancing the activity of HER. This work provides a potential strategy to construct high-performance electrocatalysts for HER over the entire pH range. Graphical abstract: Few-layer MoS2 and Pt nanoparticles co-anchored on MWCNTs for efficient hydrogen evolution reaction over a wide pH range. Image, graphical abstract